1984
DOI: 10.1038/309153a0
|View full text |Cite
|
Sign up to set email alerts
|

Two types of cholinergic innervation in cortex, one co-localized with vasoactive intestinal polypeptide

Abstract: The existence of cholinergic neuronal cell bodies in mammalian cerebral cortex was long the subject of much controversy (see ref. 1 for review). Recently, however, a specific cholinergic marker, the acetylcholine synthesizing enzyme, choline acetyltransferase (ChAT, E.C.2.3.1.6), was demonstrated by immunohistochemical methods to be present in bipolar neurones in rat cortex. Here we show that at least 80% of these intrinsic cholinergic neurones also contain immunoreactivity for vasoactive intestinal polypeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
122
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(142 citation statements)
references
References 21 publications
19
122
1
Order By: Relevance
“…,198 1) and indicated that vessels very distal in the cerebral mi crocirculation are sensitive to VIP. These vessels could be affected by VIP, which originates in peri vascular nerves or as an extracellular space neuro transmitter in cortical neurons (Eckenstein and Baughman, 1984). Our data also indicate that cere bral vessels are quite sensitive to VIP (as compared with pial vessels) .…”
Section: Discussion Vasoactive Intestinal Peptide (Vip)supporting
confidence: 56%
See 1 more Smart Citation
“…,198 1) and indicated that vessels very distal in the cerebral mi crocirculation are sensitive to VIP. These vessels could be affected by VIP, which originates in peri vascular nerves or as an extracellular space neuro transmitter in cortical neurons (Eckenstein and Baughman, 1984). Our data also indicate that cere bral vessels are quite sensitive to VIP (as compared with pial vessels) .…”
Section: Discussion Vasoactive Intestinal Peptide (Vip)supporting
confidence: 56%
“…(1986), they end on the inner layers of the adventitia in a spiral pattern. VIP has also been shown to be co-localized in cere bral tissues with choline acetyltransferase in nerves that are thought to be responsible for neurogenic cerebral vasodilation (Eckenstein and Baughman, 1984). In addition, sympathectomy does not reduce the presence of VIP in pial arteries as measured by immunofluorescence (Edvinsson et aI., 1984).…”
Section: Discussion Vasoactive Intestinal Peptide (Vip)mentioning
confidence: 99%
“…The few VIP fibers remaining in small pial branches after bilateral re moval of the sphenopalatine ganglion may possibly originate from central VIP neurons. The peptide is found in a subpopulation of cortical neurons that appear to be associated with cortical blood vessels (Eckenstein and Baughman, 1984). The physiological function of the cerebrovas cular VIP innervation is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic interneurons in the cerebral neocortex have only been observed previously in Murid rodents, with non-Murid rodents lacking these neurons (Bhagwandin et al, 2006;Kruger et al, 2012). Studies of the chemical nature of the cholinergic neocortical neurons in Rattus norvegicus, a Murid rodent, have indicated that these neurons likely co-contain vasoactive intestinal polypeptide (VIP) and gamma-aminobutyric acid (GABA) (Eckenstein and Baughman, 1984;Bayraktar et al, 1997). Thus, these neocortical neurons have multiple transmission lines that may allow them to modulate the cortical microcirculation in relation to these multiple transmission lines (Chedotal et al, 1994).…”
Section: The "Hypercholinergic" Golden Molementioning
confidence: 99%